Aptamer-Based Fluorescence Detection and Selective Disinfection of Salmonella Typhimurium by Using Hollow Carbon Nitride Nanosphere - Xinyi Liu; Jing Xu; Yang Lou; Chengsi Pan; Yin Zhang; Zhouping Wang (Biosensors, 2022)
Hollow carbon nitride nanosphere (HCNS) was synthesized via the hard template method to improve the fluorescence characteristics, drug delivery ability, and photocatalytic activity. Blue fluorescent HCNS was utilized as a quenching agent and an internal reference to combine with Cy5-labelled aptamer (Cy5-Apt), resulting in an off-on fluorescence aptasensing method for the detection of Salmonella typhimurium (S. typhimurium). Under optimum conditions, this fluorescence assay presented a linear range from 30 to 3 × 104 CFU mL−1 with a detection limit of 13 CFU mL−1. In addition, HCNS was also used as a drug carrier to load chloramphenicol (Cap) molecules. The Cap-loading amount of HCNS could reach 550 μg mg−1 within 24 h, whereas the corresponding Cap-release amount is 302.5 μg mg−1 under acidic and irradiation conditions. The integration of photocatalyst with antibiotic could endow HCNS-Cap with better disinfection performance. The bactericidal efficiency of HCNS-Cap (95.0%) against S. typhimurium within 12 h was better than those of HCNS (85.1%) and Cap (72.9%). In addition, selective disinfection of S. typhimurium was further realized by decorating aptamer. Within 4 h, almost all S. Typhimurium were inactivated by HCNS-Cap-Apt, whereas only 13.3% and 48.2% of Staphylococcus aureus and Escherichia coli cells were killed, respectively. Therefore, HCNS is a promising bio-platform for aptamer-based fluorescence detection and selective disinfection of S. typhimurium.